Islamization of Science and Campus at Ibn Khaldun University Bogor: Concepts and Implementation - Subagiya, Bahrum; Handrianto, Budi; Sauri, Sofyan (PT FORMOSA CENDEKIA GLOBAL, 2024)
Modern Western civilization has produced damage to science and many secular scientists. This challenge has elicited various responses from Muslim scholars in various parts of the world. The response was carried out with a movement of Islamization of science in various institutions of higher education. One of the institutions that responded to this challenge was Ibn Khaldun University Bogor (IKUB). On this campus, a movement called Islamization of Science and Campus (ISC) emerged. The purpose of this study is to find the idea and implementation of ISC that has been carried out by IKUB. The results of this study found that the idea of ISC conducted at IKUB was conceptualized based on three considerations, namely Islamic teachings, campus institutional aspects, and community conditions. The implementation of ISC that was initiated is, the motivation of sincere intentions because of Allah for each campus community, developing Islamic scientific traditions, instilling Islamic values in the tri dharma (teaching, research, and community service), the application of campus Islamic culture, and the example of Islamic akhlak from leaders at various levels.